Simulation of silvicultural scenarios and economic efficiency for maritime pine (Pinus pinaster Aiton) wood-oriented management in centre inland of Portugal - Alegria, C.M.M. (2012)
Seven silvicultural scenarios for pure and even aged maritime pine stands were simulated using a diameter class growth and yield model, for three levels of site index (low, medium and high). Total and merchantable yield along rotation and mean annual increment at rotation age were simulated. Revenue obtained from sale of standing timber (three commercial thinning and final harvest) was estimated. Costs paid for stand establishment (site preparation and plantation) and treatments (release, pre-commercial thinning and pruning) were also estimated. For each scenario, a cash-flow was simulated and economic efficiency was assessed using the net present value of an infinitive series of rotations (NPVIS) and the internal rate of return (IRR). The economic analysis results proved the selection of an intensive management stand prescription that is used as a guide for reforestation projects, using artificial regeneration by plantation, when the main goal is round wood yield. For areas of natural regeneration, a fully stocked stand prescription, pulp wood yield oriented, was selected. This prescription enables saving in site preparation and plantation costs, being at the moment the most suitable for the existing naturally regenerated maritime pine stands of Portuguese private forest areas.